Effectiveness of Lavender Aromatherapy on Reducing Pain Intensity after 24 Hours Post Sectio Caesarea - Ita Herawati; Putri Nurmala Sari; Budi Ermanto (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims: Based on the 2018 Basic Health Research (Riskesdas) data, there was 81.5 percent of normal deliveries, and 17.6 percent of them were born by Section Caesarea. Delivery by SC can provide higher complications than giving birth vaginally or normally. One of the conditions that cause patient discomfort is pain. One of the non-pharmacological therapies to treat post-SC pain is lavender aromatherapy. Methods: Quantitative method employing a quasi-experimental design with a pre-post test design in one group (pretest-posttest design in one group). By diffusion, using a diffuser to emit a fragrant fragrance, a dose of 5-10 drops diluted with 20 ml of water is administered once every 60 minutes. This study's demographic consisted of post-Caesarean section patients treated at YPK Mandiri Hospital in December 2022. The sampling method was incidental sampling, and the sample size was forty respondents. Results: Prior to receiving lavender aromatherapy, there were 38 respondents with moderate pain (95%) and two respondents with mild pain; after receiving lavender aromatherapy, the intensity of pain decreased to mild. 39 respondents (97.5%) and 1 respondent (2.5%) continued to experience moderate pain. Aromatherapy with lavender is efficacious in reducing pain 24 hours after SC (Asymp. Sig). Conclusions: Lavender aromatherapy is effective in reducing pain 24 hours after SC; therefore, it is anticipated that lavender aromatherapy will become the primary therapy before patients are given pharmacological therapy, such as pain-relieving medications.